Impact of Different Relative Humidities on In vitro Growth And Sporulation of Entomopathogenic Fungal Isolates of Beauveria Species - Palem, P.C Padmini (International Journal of Pharmaceutical & Biological Archive, 2010)
Thirty isolates of Beauveria species were evaluated for in vitro growth and sporulation at five different relative humidities at a constant temperature of 30ÂºC. Only twenty isolates could grow at 60%, 63%, 75% and 85% relative humidities, while 91% relative humidity did not permit growth of ten isolates. On the other hand, eleven isolates only out of thirty displayed sporulation. Optimum RH for Beauveria isolates for growth and sporulation appeared to be 60%.